Metformin in pregnancy to avert gestational diabetes in women at high risk: Meta‐analysis of randomized controlled trials. (31st October 2019) - Doi, Suhail A.R.; Furuya‐Kanamori, Luis; Toft, Egon; Musa, Omran A.H.; Islam, Nazmul; Clark, Justin; Thalib, Lukman
Summary: Previous randomized and observational studies on the efficacy of metformin in pregnancy to reduce incident gestational diabetes mellitus (GDM) in women at high risk (obesity, polycystic ovary syndrome [PCOS], or pregestational insulin resistance) have been conflicting and several groups are planning further randomized controlled trials (RCTs) to answer this question conclusively. This work assesses the efficacy of metformin in pregnancy to avert one outcome—incident GDM in women at high risk. We included RCTs comparing metformin with usual care or placebo controls in terms of incident GDM and recruiting women at high risk during early pregnancy. Eleven eligible trials enrolled 2370 adult women whose intervention arm consisted of metformin started at conception or before 20 weeks of gestation. Risk of GDM was similar in intervention compared with controls (risk ratio [RR] 1.03; 95% confidence interval [CI], 0.85‐1.24). The data were of sufficient quality meeting the criteria for consistency and directness. We conclude that metformin does not contribute to averting the GDM outcome in women at high risk when initiated in pregnancy. The evidence provided by this synthesis affirms that further broad clinical trials investigating this question are no longer needed.